A survey of photocatalytic materials for environmental remediation - Di Paola, Agatino; García-López, Elisa; Marcì, Giuseppe; Palmisano, Leonardo (Journal of hazardous materials, 2012)
[Display omitted] ► Photocatalytic materials for water and air decontamination. ► Modified and nanoassembled TiO2. ► Photocatalysts alternative to TiO2 for environmental remediation. ► Binary, ternary and quaternary photocatalysts. Heterogeneous photocatalysis is an advanced oxidation process which has been the subject of a huge amount of studies related to air cleaning and water purification. All these processes have been carried out mainly by using TiO2-based materials as the photocatalysts and ca. 75% of the articles published in the last 3 years is related to them. This review illustrates the efforts in the search of alternative photocatalysts that are not based on TiO2, with some exceptions concerning particularly innovative modifications as nanoassembled TiO2 or TiO2 composites with active carbon, graphite and fullerene. Papers reporting preparation, characterization and testing of binary, ternary and quaternary compounds, have been reviewed. Despite many of these photocatalysts being effective for the photodecomposition of many pollutants, most of them do not allow a complete mineralization of the starting compounds, differently from TiO2.